A Systematic Approach for the Modeling of Replicated Foams. Issue 6 (3rd October 2014) - Rahimi, Mehrad Mousavi; Shahbeyk, Sharif
<x xml:space="preserve">Abstract</x> This paper proposes a numerical framework for realistic simulation of replicated foams. The method is inspired by the actual processes used in the manufacturing of this class of cellular materials. Accordingly, an assembly of space‐holders is generated first, then the physical process of cold isostatic pressing is simulated and, finally, the structure resulting from the leaching process is modeled using a voxel‐like finite element model and an efficient inverting algorithm. A simple yet effective solution for the simulation of the influence of infiltration pressure on the microstructure of foam is also suggested. Next, the numerical approach is verified using the experimental results of a set of replicated aluminum foams whose preforms were monomodal spherical salt grains. Samples with various relative densities are modeled and their elastic and yield properties are compared to those of tested samples from the literature. Satisfactory agreement has been achieved, which confirms the usefulness of the proposed approach.